1970
DOI: 10.3329/jbcps.v24i2.147
|View full text |Cite
|
Sign up to set email alerts
|

Oral Versus Vaginal Misoprostol for Induction of Labour

Abstract: It is sometimes difficult to select the most effective, easy to use, safest, widely accepted and less expensive method for induction of labour and thereby spontaneous vaginal delivery. Prostaglandin E1 analogue ie misoprostol as a successful method both in oral and vaginal form has been used for induction of labour. The present study was conducted with an aim to compare the efficacy and safety of oral and vaginal administration of misoprostol tablets for cervical ripening and induction of labour in pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…These results were consistent with those of N. Sultana et al, [8], where they reported a 4% rate of hyperstimulation in vaginal group. These results were also consistent with those of Khadija et al, [7], where they reported a 1% rate of hyperstimulation in vaginal group.…”
Section: Maternal Complicationssupporting
confidence: 83%
See 2 more Smart Citations
“…These results were consistent with those of N. Sultana et al, [8], where they reported a 4% rate of hyperstimulation in vaginal group. These results were also consistent with those of Khadija et al, [7], where they reported a 1% rate of hyperstimulation in vaginal group.…”
Section: Maternal Complicationssupporting
confidence: 83%
“…These results were consistent with those of N Sultana et al, [8], where failed Induction rate was 8% in vaginal group and it was 6% in oral group.…”
Section: Failed Inductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Gestational diabetes 4. PROM 50 μg sublingually 25 μg vaginally 418 eligible 280 excluded 138 included Compare the efficacy and safety of 50 mg of sublingual misoprostol with 25 mg of vaginal misoprostol administered for labor induction at term Sultana (2006) [ 55 ] 1. Gestational age 37–42 w 2.…”
Section: Appendixmentioning
confidence: 99%